Assessing wastewater-based epidemiology for the prediction of SARS-CoV-2 incidence in Catalonia - Bernat Joseph-Duran; Albert Serra-Compte; Miquel Sàrrias; Susana Gonzalez; Daniel López; Clara Prats; Martí Català; Enric Alvarez-Lacalle; Sergio Alonso; Marina Arnaldos (Scientific Reports, 2022)
Abstract While wastewater-based epidemiology has proven a useful tool for epidemiological surveillance during the COVID-19 pandemic, few quantitative models comparing virus concentrations in wastewater samples and cumulative incidence have been established. In this work, a simple mathematical model relating virus concentration and cumulative incidence for full contagion waves was developed. The model was then used for short-term forecasting and compared to a local linear model. Both scenarios were tested using a dataset composed of samples from 32 wastewater treatment plants and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) incidence data covering the corresponding geographical areas during a 7-month period, including two contagion waves. A population-averaged dataset was also developed to model and predict the incidence over the full geography. Overall, the mathematical model based on wastewater data showed a good correlation with cumulative cases and allowed us to anticipate SARS-CoV-2 incidence in one week, which is of special relevance in situations where the epidemiological monitoring system cannot be fully implemented.